2017
DOI: 10.21767/2471-9676.100030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High HIV/AIDS Risk Sexual Behaviors: Comparison Study among Cameroonian and Gabonese Youth Aged 15-24 years

Abstract: Background: Cameroon and Gabon are among the most highly HIV/AIDS prevalent Central and West African countries with unwavering HIV epidemic. The spread of HIV, among youth in Gabon and Cameroon, is believed to be driven by unsafe heterosexual intercourse. However, no research has been done to investigate the predicting factors of risk sexual behaviors among the youth of the two countries. Therefore, the aim of this study was to investigate the predicting factors of highrisk sexual behaviors among 15-24 aged yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…That suggests a high tendency to keep a few trusted sexual partners with whom young females believe they can continue to enjoy unprotected sex (Odimegwu & Somefun, 2017), thinking they are safe. Previous studies also revealed that unmarried youths who are not into marital vow have greater chances of engaging in risky sexual behaviour (Chawla & Sarkar, 2019;Hadish et al, 2017;Wendland et al, 2018). However, what passes for risky sexual behaviour could be examined through the lens of marital status as suggested by this study in which ever-married young people were more likely to not use protection (during their first and last sexual intercourse) probably because of their desire for children.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…That suggests a high tendency to keep a few trusted sexual partners with whom young females believe they can continue to enjoy unprotected sex (Odimegwu & Somefun, 2017), thinking they are safe. Previous studies also revealed that unmarried youths who are not into marital vow have greater chances of engaging in risky sexual behaviour (Chawla & Sarkar, 2019;Hadish et al, 2017;Wendland et al, 2018). However, what passes for risky sexual behaviour could be examined through the lens of marital status as suggested by this study in which ever-married young people were more likely to not use protection (during their first and last sexual intercourse) probably because of their desire for children.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the vast amount of studies geared towards investigating and understanding risky sexual behaviours among young people, understanding the processes linking risky sexual behaviours with its predictors remains limited in Nigeria. Previous studies have identified numerous factors associated with risky sexual behaviours among young people including age and gender, with men having higher odds of engaging in unprotected sexual intercourse (Abosetugn, Zergaw, Tadesse, & Addisu, 2015;Ganczak, Czubinska, Korzen, & Szych, 2017;Hadish, Mao, Gong, Hadish, & Tesfamariam, 2017;Noubiap et al, 2015;Sambisa, Curtis, & Stokes, 2010;Sekoni & Soyanwo, 2014;Shek, 2013). Besides, the relationship status of an individual has also been found to significantly predict sexual behaviour; single people have higher chances of having unprotected sex (Ganczak et al, 2017;Hadish et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived health status was assessed by asking the question “how is your health in general?” very good was scored 3, good was scored 2 and fair was scored 1 [ 13 ]. Sexuality was analysed as sexual behaviour which was categorized as risky and non-risky sexual behaviour [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pressing among these factors is the population knowledge of HIV/AIDS knowledge [16,26]. The extent of knowledge on the implications of the deadly virus have been attributed to exposure to mass media, social media, utilisation of voluntary counselling unit, sociocultural, drug and illicit substance abuse economic and demographic factors [5,9,[27][28][29][30].…”
mentioning
confidence: 99%